Simple surface plasmon resonance bio-sensor for the quantification of recombinant human epidermal growth factor (rhEGF) in expanded bed recovery - Faizal Wong, Fadzlie Wong (2010)
The conventional quantification assays used monitor the performance of protein downstream processing are typically not user friendly as it is laborious, time consuming and costly. At the same time, the emergence of multi-modal adsorbent, streamline Direct HST (1.8 g/cm3) to handle high ionic strength feedstock can potentially improve the recovery of protein in expanded bed adsorption (EBA). Hence, the objectives of the study are to develop a reliable quantification assay for recombinant human epidermal growth factor (rhEGF) by Surface Plasmon Resonance and to examine its application for the monitoring of rhEGF recovery by HST adsorbent in EBA. It was developed based on the BIAcore 3000 instrument with anti-rhEGF antibody immobilized on the CM5 chip. The performances of the assay were: assay linearity (25 to 250 ng/mL), accuracy (within 10% recovery of target), precision (below 3.4% CV), intra- and inter-assay precision (less than 20% CV) and rhEGF onto Streamline HST was at pH 4 in acetate buffer without the NaC1 or at high (1.8 M) NaC1 concentration as determined from the batch binding experiment. The electrostatic interaction, hydrophobic interaction and the hydrogen bonds responsible for this. As for the elution, potassium buffer with pH 12 used exploiting the effect of electrostatic repulsion. The effect of cells (Escherichia coli and Pastoris pastoris) on the performance of HST adsorbent in capturing rhEGF was also being examined by fitting the adsorption into the langmuir isotherm. The thermodynamic parameters: maximum binding capacity (qm) and equilibrium dissociation constant (Kd) are little affected as the concentration of these biomass increased from 0 to 4.73 % w/v. the result showed that the adsorption level was not a strong function of the biomass concentration. Next, the feasibility of using the HST adsorbent to capture rhEGF in EBA was finally tested using the single component sample (only rhEGF) with the presence of biomass (4.73 % w/v E. coli or P. pastoris). Fastline 10 column (Upfront, Denmark) was used to handle 20 mL of sample volume with adsorbent settled bed height of 2 cm (1.6 mL). the results demonstrated that a consistent yield can be obtained even with the presence of cells (97.38% for control, 96.94% for P. pastoris and 96.43% for E. coli) and a stable bed can be achieved, suggesting that no interference of adsorption by biomass occurred. In conclusion, the major contributions of the study are the development of reliable SPR quantification assay and the EBA process template that is useful for rhEGF purification from real feedstock.